2000
DOI: 10.1007/s002480000018
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Geobacter Species in Response to Stimulation of Fe(III) Reduction in Sandy Aquifer Sediments

Abstract: Engineered stimulation of Fe(III) has been proposed as a strategy to enhance the immobilization of radioactive and toxic metals in metal-contaminated subsurface environments. Therefore, laboratory and field studies were conducted to determine which microbial populations would respond to stimulation of Fe(III) reduction in the sediments of sandy aquifers. In laboratory studies, the addition of either various organic electron donors or electron shuttle compounds stimulated Fe(III) reduction and resulted in Geoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
161
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(174 citation statements)
references
References 45 publications
12
161
1
Order By: Relevance
“…The most important consequence of AQDS supplementation in soil microcosms was its stimulation on the growth of Geobacter species, and the extent of enrichment positively correlated to the amount of AQDS reduced. This was similar to the previous studies that have reported the enrichment of Geobacter species in aquifer sediments by the addition of humics and other extracellular quinones [43]. The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27].…”
Section: Discussionsupporting
confidence: 89%
“…The most important consequence of AQDS supplementation in soil microcosms was its stimulation on the growth of Geobacter species, and the extent of enrichment positively correlated to the amount of AQDS reduced. This was similar to the previous studies that have reported the enrichment of Geobacter species in aquifer sediments by the addition of humics and other extracellular quinones [43]. The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27].…”
Section: Discussionsupporting
confidence: 89%
“…In a similar study with Black Sea sediment clone libraries from the highest dilution of the acetateoxidizing manganese reducers revealed 16S rRNA gene sequences related to Arcobacter and Pelobacter within the Desulfuromonadales and additional, after subcultivation on lactate, to Shewanella , which were related to the sequences of this study (90 to 497% sequences identity to the respective sequences) ( Figure 5). Shewanella and members of the Desulfuromonadales are two groups with the ability to reduce iron and manganese, which are recovered frequently through cultivation for example, with iron oxides as electron acceptor or acetate as electron donor (Caccavo et al, 1992;Venkateswaran et al, 1998;Snoeyenbos-West et al, 2000;Holmes et al, 2002;Vandieken et al, 2006a). S. putrefaciens is one of the few strains isolated directly by manganese oxide reduction (Myers and Nealson, 1988;Nealson et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…All members of the Desulfuromonadales are able to reduce iron and manganese oxides and are also frequently found in clone libraries of marine sediments (for example, Ravenschlag et al, 1999;Bowman and McCuaig, 2003;Mu mann et al, 2005). Desulfuromonadalesrelated organisms can be easily enriched in sediments or microbial fuel cells by acetate addition (Snoeyenbos-West et al, 2000;Bond et al, 2002; Manganese-reducing bacteria in marine sediments V Vandieken et al Holmes et al, 2002;Holmes et al, 2004;Vandieken et al, 2006a) but have also been identified as ironreducing bacteria by cultivation-independent SIP studies with 13 C-acetate in rice field soil and uranium-contaminated aquifer (Chang et al, 2005;Hori et al, 2010). Our finding of Desulfuromonadales in MPN enrichments coincided with their detection in clone libraries of heavy SIP fractions.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it is not possible to accurately assess the impact of changes in FeRB abundance on the kinetics of Fe(III) oxide reduction in the OM addition experiment. Refinement of MPN procedures for enumeration of FeRB (e.g., through use of natural media; Vester and Invorsen 1998) and/or application of molecular genetic techniques for non-culture-based estimation of FeRB abundance (e.g., MPN-PCR (polymerase chain reaction); Anderson et al 1998;Rooney-Varga et al 1999;Snoeyenbos-West et al 2000) will be required in order to link variations in FeRB biomass to the bulk kinetics of Fe(III) oxide reduction in aquatic sediments.…”
Section: Discussionmentioning
confidence: 99%